2022
DOI: 10.1002/cam4.4805
|View full text |Cite
|
Sign up to set email alerts
|

Novel protein contact points among TP53 and minichromosome maintenance complex proteins 2, 3, and 5

Abstract: Objective Identify protein contact points between TP53 and minichromosome maintenance (MCM) complex proteins 2, 3, and 5 with high resolution allowing for potential novel Cancer drug design. Methods A next‐generation sequencing‐based protein–protein interaction method developed in our laboratory called AVA‐Seq was applied to a gold‐standard human protein interaction set. Proteins including TP53, MCM2, MCM3, MCM5, HSP90AA1, PCNA, NOD1, and others were sheared and ligated into the AVA‐Seq system. Protein–protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
(173 reference statements)
1
3
0
Order By: Relevance
“…In 8 independent experiments, we identified 33 proteins that interacted with G245D mutp53 in UM-SCC-1 cells (Supplementary Data 1 ). Many of them, such as the p63 40 , FAM83A 41 , FUBP1 42 , TGM2 43 , SNRPN 44 , MCM5 45 , and MCM7 46 , were previously shown to interact with wtp53 and/or mutp53s, which validated the reliability of our approach. Metascape enrichment analysis 47 of purified G245D mutp53-interacting proteins showed that the gene ontology (GO) term “regulation of DNA replication initiation” involving MCM5, MCM7, and WRNIP1 was significantly enriched (Fig.…”
Section: Resultssupporting
confidence: 66%
“…In 8 independent experiments, we identified 33 proteins that interacted with G245D mutp53 in UM-SCC-1 cells (Supplementary Data 1 ). Many of them, such as the p63 40 , FAM83A 41 , FUBP1 42 , TGM2 43 , SNRPN 44 , MCM5 45 , and MCM7 46 , were previously shown to interact with wtp53 and/or mutp53s, which validated the reliability of our approach. Metascape enrichment analysis 47 of purified G245D mutp53-interacting proteins showed that the gene ontology (GO) term “regulation of DNA replication initiation” involving MCM5, MCM7, and WRNIP1 was significantly enriched (Fig.…”
Section: Resultssupporting
confidence: 66%
“…The AVA-Seq method is a powerful tool to detect protein fragment-fragment interactions (8, 25, 29) and full-length protein-protein interactions. Here, we showed a novel application combining the AVA-Seq system and Oxford Nanopore Technologies MinION platform to detect full-length protein interactomes.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that various protein-protein interaction methods do not recover all interactions. So even well-studied pathways such as the WNT pathway would benefit from analysis with new methods [19, 20]. The all-vs-all sequencing (AVA-Seq) method is a novel approach for detecting PPIs.…”
Section: Introductionmentioning
confidence: 99%